Can Contextual Teaching and Learning (CTL) Revolutionize Cadets’ Speaking Skills in Maritime English? - Limbong, Sunarlia; Palayukan, Novianty; Djajasasana, Egbert Edward; Tandibura, Frans (VELES Voices of English Language Education Society, 2024)
Effective English communication is vital in the global maritime industry. Maritime English, a branch of English for Specific Purposes (ESP), addresses the needs of maritime professionals. Contextual Teaching and Learning (CTL) uses real-life scenarios, making it ideal for vocational training. This means practicing real shipboard situations for maritime cadets, leading to effective learning. This study investigates the effectiveness of Contextual Teaching and Learning (CTL) on cadets’ speaking skills when learning English for Specific Purposes (ESP) instructional materials. The study applied a quasi-experimental method with a nonequivalent group design, involving 48 cadets from the deck study program at the Merchant Marine Polytechnic of Makassar, Indonesia. The results indicate a significant improvement in the pretest-posttest scores, analyzed using a statistical test with the prerequisite data being normally distributed. The hypothesis test results, with a significance value of 0.000, confirm that there were differences in the speaking skills of the cadets at the Merchant Marine Polytechnic of Makassar after applying the CTL model in English for Specific Purposes (ESP) instructional materials. The findings highlight that the CTL model positively impacts and optimally influences the teaching and learning process in speaking skills when cadets learn ESP materials. This approach increases cadets' confidence and encourages them to be active learners based on their real experiences.